Active assessment of fitness and performance in a general population - Brent Winslow; Aravind Natarajan; Samantha Mravca; Justin Julian Duong; Salahuddin Choudhary; Tracy Norman Giest (Frontiers in Sports and Active Living)
Much of the current worldwide morbidity results largely from unhealthy diet, inactivity, and inadequate access to health resources. Improving body composition, strength, endurance, and cardiorespiratory fitness is associated with increased longevity and function, but current fitness assessments are largely qualitative and episodic. The current study sought to examine the feasibility of various bodyweight exercises in a general population, compare exercise performance metrics to reference measures, and develop a comprehensive fitness and performance assessment battery tied to longevity metrics. A group of adult research subjects (n = 152) from a convenience sample performed a series of 13 exercises and reference tests across balance, strength, endurance, flexibility, and cardiorespiratory fitness. While the majority of participants could perform all exercises, sex and age-related differences were observed in exercise performance. Isotonic exercises, such as push ups or floor triceps dips correlated more closely with reference measures than isometric exercises, such as squat and plank holds, which were associated with ceiling effects. Using this data, a comprehensive active assessment is proposed to screen for changes to fitness and provide individualized recommendations.